THE EFFECTIVENESS OF USING TOOTHPASTE CONTAINING ROBUSTA COFFEE BEAN EXTRACT IN INHIBITING THE FORMATION OF DENTAL PLAQUE - Rina Nanda Prasasti; Desi Sandra Sari; Peni Pujiastuti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Periodontal disease is caused by the interaction between pathogenic bacteria and plaque, without the accumulation of plaque, periodontal disease will not appear. Plaque will be visible one to two days if no oral cleaning steps are taken. The combination of antimicrobial therapy such as antibiotics and mouthwash as well as mechanical therapy such as scaling and root plain gives more effective results. However, if done in the long term it will cause resistance. To overcome this, alternative materials are needed that are used to inhibit bacterial growth, one of which is robusta coffee beans. The content of robusta coffee bean extract contains phenolic and flavonoid compounds that function as antibacterials that work by disrupting the function of the cytoplasmic and cytoplasmic membranes of bacteria.Method: In this study, 6 groups were used, namely KN, K-, K+, KP 25%, KP 50%, and KP 75%. The gingivitis model was made with wire using ligation technique for 3 days, then toothpaste was applied, brushing process, and disclosing agent was given, and the plaque index calculation was PHP (Personal Hygiene Performance). The data obtained were then analyzed using the Kruskall-Wallis test followed by the Mann-Whitney test.Result: The Robusta coffee bean extract toothpaste group at a concentration of 75% experienced a significant reduction in plaque compared to the negative control group and the 25% treatment group (p<0.05), but there were no significant differences or had the same ability when compared to the experimental group. 50% treatment group, normal control group and positive control group.Conclusion: The 75% concentration of Robusta coffee bean extract found in toothpaste is proven to be effective in inhibiting the formation of dental plaque.